Soil Microbial Community and Litter Quality Controls on Decomposition Across a Tropical Forest Disturbance Gradient - Elias, Dafydd M. O.; Robinson, Samuel; Both, Sabine; Goodall, Tim; Majalap-Lee, Noreen; Ostle, Nick J.; McNamara, Niall P. (Frontiers in Forests and Global Change, 2020)
Industrial logging and agricultural expansion are driving rapid transformations of tropical ecosystems, modifying patterns in above – ground plant and below – ground microbial communities. However, the extent to which these changes in biodiversity drive modifications of ecosystem process rates such as leaf litter decomposition is poorly understood. To determine the relative effects of changes to the chemical quality of litter and shifts in microbial decomposers on leaf litter decomposition rates, we performed a controlled, reciprocal transplant, litter decomposition experiment across a tropical land - use disturbance gradient. Litter mixtures and soils were collected from old growth forest, moderately logged forest, heavily logged forest and oil palm plantation in Sabah, Malaysia, and combined in a fully crossed, factorial microcosm experiment maintained under controlled environmental conditions. We found that whilst litter quality was the most important predictor of litter mass loss, soil origin was also significant, explaining between 5.17 – 15.43 % of total variation. Microbial decomposer communities from old growth forest had greater functional breadth relative to those from logged forests and oil palm plantation as all litter types decomposed faster when combined with old growth soil. The most chemically recalcitrant litter (lowest N, highest lignin, lignin:N and C:N ratio) from moderate logged forest decomposed faster when combine with its “home” soil (Home – Field Advantage) whilst the most labile litter from oil palm decomposed slowest when combined with its “home” soil. This was correlated with lower total soil microbial biomass. Taken together, these findings demonstrate that whilst litter quality regulated rates of litter decomposition across the disturbance gradient, soil microbial decomposer communities were functionally dissimilar between land uses and explained a significant proportion of variation. The impact of disturbance on soil, including microbial community structure, should be considered alongside changes to plant communities when assessing effects on crucial ecosystem processes such as decomposition.